A real time vehicle management system implementation on cloud computing platform. (2017) - Lin, Hua-Yi; Doong, Jiann-Gwo; Hsieh, Meng-Yen; Li, Kuan-Ching
This study attempts to use the high-speed computing capability of cloud computing and smart phones to achieve a vehicle management system running on moving cars. Our researches exploit smart phones or tablet PCs as a car machine that provides an application of location-based services on the mobile device with global position system (GPS), wireless camcorder, Google-map, visualisation information, and graphical presentation to provide personalised services (Zhang et al., 2010; Sultan, 2010). This study allows users instantly to access the information and manage the movement of cars. Additionally, the location of golf carts, surrounding environment and personnel information are transmitted through a wireless network to the monitor centre. Thus monitor centre can achieve real-time services, motorcade managements and caddy caring services. If the proposed mechanism performs well, this study will be extended to some other applications in the near future.